THE RELATIONSHIP BETWEEN PSYCHOLOGICALl CAPITAL AND READINESS FOR CHANGE ON THE TRANSFORMATION PROGRAM OF STATE OWN COMPANY AND PRIVATE COMPANY IN JABODETABEK AREA: LEADERSHIP STYLE AS MEDIATOR - Soeharso, Silverius Yoseph; Dewayani, Kristiana (Accounting Department,, 2020)
AbstractManuscript type: Research paper.Research aim: The aim of this research research was to examine whether leadership style mediated the relationship between psychological capital and readiness for change in the process of organizational transformation of state-owned and private companies in Jabodetabek, Indonesia.Design/ Methodology/ Approach: A survey was conducted on 149 employees from 256 of private companies and state own companyâ€™s. There were three instruments used: the scale of readiness for change from Hanpachern et.al (1997) and Armenakis et.al (1999; 2013), the scale of psychological capital from modified by Dewayani (2014), and the scale of leadership (transformational and transactional) from Bass and Riggio (2006).Â All three of these measurement scales have strong reliability scores between .82 to .91. The data was analysed by SEM (Structural Equation Modeling) and the STATCAL statistical program.Â Research findings: The results revealed that the perception of employee self-leadership fully mediated the relationship between psychological capital and readiness for change.Theoretical contribution/ Originality: It is suggested that in a process of transformation, the role of both the transactional and transformational leadership styles is important, but transformational leadership has more significant influence in the process of organizational transformation. although in theory and previous studies have stated that transformational leadership is more significant than transactional leadership in the process of organizational transformation, in this study shows the level of position in the organizational hierarchy also influences. In this study shows that at the staff level especially sacrificed proves that the transactional leadership style is more influential than the transformational leadership style. Thus, in the process of organizational transformation both leadership styles need to be applied depending on the group of employees that will be influenced. The lower the position, the more the need to apply transactional leadership style, the higher the position the possibility of the need for transformational leadership style.Practitioner/ Policy implication: From the description above, readiness for change can be interpreted as psychological and physical readiness, to understand the need for changes needed by the organization, individual beliefs to be able to implement planned or proposed changes and to believe that these changes can have a positive impact, both for themselves and organization.Research limitation: The sample size is too small to generalise the findings to the larger population. In addition to samples that are too small to be generalized to a larger population, this study also only involves samples in Jabodetabek so that it is less representative of the population in Indonesia, other than that it is only taken from the staff level so that the managerial level is not examined in this study.Keywords: Leadership, Psychological Capital, Readiness for Change, Indonesian Companies.